2021
DOI: 10.18632/aging.203544
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of POCD caused by sevoflurane in mice: cognitive impairment induced by cross-dysfunction of iron and glucose metabolism

Abstract: Sevoflurane (Sev) is a commonly used anesthetic in hospitals that can cause neurotoxicity. Postoperative cognitive dysfunction (POCD) is a common clinical problem induced by some anesthetics. However, the exact mechanism of neurotoxicity induced by Sev is unclear. Here we studied a new mechanism of POCD induced by Sev. We treated 15-month-old mice with 2% Sev for 6 hours, and we had found that Sev causes POCD. Using isobaric tags for relative and absolute quantitation (iTRAQ), we found that the transporter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
4
28
0
1
Order By: Relevance
“…Mitochondrial dysfunction has been described for both anesthetics using multiple experimental approaches [ 12 , 30 , 32 , 45 , 53 , 54 , 55 ]. In particular, direct inhibition of mitochondrial complexes I, II, and III by volatile anesthetics have been involved in presynaptic modulation, mitochondrial depolarization, decreased ATP production, and preconditioning [ 13 , 14 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction has been described for both anesthetics using multiple experimental approaches [ 12 , 30 , 32 , 45 , 53 , 54 , 55 ]. In particular, direct inhibition of mitochondrial complexes I, II, and III by volatile anesthetics have been involved in presynaptic modulation, mitochondrial depolarization, decreased ATP production, and preconditioning [ 13 , 14 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mitochondrial impairment was induced by sevoflurane in different neonatal, aged, and Alzheimer’s disease animal models. Among others, mechanisms involved were mitophagy inhibition [ 30 ], lower oxidative phosphorylation [ 31 ], iron/glucose metabolism-derangement [ 32 ], and mitochondrial depolarization via complex-V inhibition [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating clinical evidences also showed that PNDs could occur irrespective of the anesthetic technique used, suggesting that surgery may play a prominent role in the development of postoperative cognitive deficits [ 86 88 ]. However, some studies reported that sevoflurane alone could induce cognitive decline in aged animals [ 89 , 90 ]. Possible reason for this discrepancy is the different duration of general anesthetics used.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reason for this discrepancy is the different duration of general anesthetics used. The animals that exposed to 2% sevoflurane for 5–6 h exhibited impaired cognitive function [ 89 , 90 ]. While the use of general anesthetics no more than 1 h neither induce peripheral or centrally proinflammatory cytokine or NMDARs changes [ 10 , 35 , 63 , 85 , 91 ], nor lead to postoperative cognitive dysfunction [ 10 , 35 , 63 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have also proven that the occurrence and development of POCD were related to the choice of anesthetics, such as the intravenous anesthetics etomidate and propofol, and the inhaled anesthetic, sevoflurane, all of which have become common induction drugs for constructing animal models of POCD in the field of basic research. Increased attention has been focused on specific induction mechanisms, such as early neuroinflammation, nerve cell death, and sevoflurane-induced cross dysfunction of iron and sugar metabolism in mouse brain cells, which led to apoptosis, along with the corresponding diagnosis and treatment strategies ( Cui et al, 2018 ; Li D. et al, 2020 ; Ge et al, 2021 ; Liu et al, 2021 ). The results of various studies on the effects of different anesthesia methods and anesthetics on postoperative cognitive function have been different, even contradictory, and the reasons for the conflicting results are still inconclusive.…”
Section: Potential Mechanisms Of Central Neuroinflammation Occurrencementioning
confidence: 99%